An Ability in Translating Recount Text by Using Translating Strategies - Mardin Silalahi; Rohdearni Wati Sipayung (BIRCU, 2021)
This research is focused on the ability of the students in translating a recount text by using translating strategies at the first grade students of SMA Swasta Yayasan Perguruan Keluarga (YPK) Pematangsiantar. This study tries to find out: 1) The translation strategy that are used by the students in the translating of a recount text; 2) The translation strategy that is mostly used by the students in the translating of a recount text; 3) The students’ perception towards the translating tasks as an alternative task to enhance their reading habit and vocabulary. From the data analysis it can be concluded that: 1) In translating the recount text entitled Borobudur, especially in dealing with certain words, the students employ ten translation strategy. These strategies are taken from the Newmarks’ translation strategy (1988: 81-93). The strategies which are applied by the students in this study are the transference strategy, the naturalization strategy, the cultural equivalent strategy, the shift or transposition strategy, the modulation strategy, the recognized translation strategy, the compensation strategy, the expansion strategy, the couplets strategy, and the triplets strategy; 2) The cultural equivalent strategy is the one which is mostly used by the students in translating the text. Based on Newmark (1988: 82-83), this strategy is commonly found in translating popular fiction texts; 3) The students’ perception towards the translating tasks which are given by their teacher is that the translating tasks can help them enhance their reading habit and increase their vocabulary. The reason behind this perception is because they admit that they even do not read English texts unless their teacher has them do so. In this case, it is obviously seen that the students agree that the translating task is an alternative task to make them read English texts. Although in the reality translating task is neglected by many educators, since it is included into one of the characteristics of the Grammar Translation method which is assumed only to focus on knowing grammar rules, remember vocabularies, and produce a good translation of target language.